2020
DOI: 10.3390/rs12142199
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Aboveground Biomass of Shrubs Using Spectral and Structural Metrics Derived from UAS Imagery

Abstract: Shrub-dominated ecosystems support biodiversity and play an important storage role in the global carbon cycle. However, it is challenging to characterize biophysical properties of low-stature vegetation like shrubs from conventional ground-based or remotely sensed data. We used spectral and structural variables derived from high-resolution unmanned aerial system (UAS) imagery to estimate the aboveground biomass of shrubs in the Betula and Salix genera in a montane meadow in Banff National Park, Canada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 87 publications
0
5
1
Order By: Relevance
“…In this study, CV is a proxy to DW, and CV×EVI a proxy to FW. Other studies similarly used VIs [21,26] or combination of structural and spectral information [43,51,52] in modelling biomass, which is also a proxy-based approach. It could not be claimed with the available data in the study that the reported simple linear model relationships would hold exactly same every year, nevertheless the metrics CV and CV×EVI could certainly be used as a proxy to screen crop genotypes with higher or lower biomass and monitor their growth patterns over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, CV is a proxy to DW, and CV×EVI a proxy to FW. Other studies similarly used VIs [21,26] or combination of structural and spectral information [43,51,52] in modelling biomass, which is also a proxy-based approach. It could not be claimed with the available data in the study that the reported simple linear model relationships would hold exactly same every year, nevertheless the metrics CV and CV×EVI could certainly be used as a proxy to screen crop genotypes with higher or lower biomass and monitor their growth patterns over time.…”
Section: Discussionmentioning
confidence: 99%
“…Using both spectral (VIs) and structural (surface models) information obtained from UAVs could be a useful approach for not only estimating biomass but also other crop traits such as leaf area index, chlorophyll and nitrogen content, plant lodging, plant density, and counting head numbers. Though few studies have combined spectral (VIs) and structural (CHMs) data in estimating biomass in barley [43], pastures [51], and shrubs-dominated ecosystems [52]. However, the potential of combining spectral and structural information for the estimation of dry and fresh biomass in the agronomically important food crop wheat is yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Although digital cameras do not directly record reflectance, the increased use of structure-from-motion in various research disciplines has led to the use of imagery from consumer cameras for calculating spectral indices (e.g. Torres-Sánchez and others, 2014; Poley and others, 2020). Unlike true reflectance data, the digital signature of consumer cameras is affected by differences in camera settings and lighting conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Equipped with highresolution sensors and advanced image processing techniques, UAVs can capture high-quality remote sensing imagery, offering comprehensive data on shrub vegetation [38,39]. They are capable of capturing extensive areas of shrub coverage from a high-altitude overhead perspective, enabling the rapid and accurate identification and extraction of shrub objects [37,[40][41][42]. Additionally, UAVs have higher spatial resolution and flexibility compared to traditional aerial remote sensing techniques, allowing for the capture of finer details of shrub structure and characteristics [43].…”
Section: Introductionmentioning
confidence: 99%